2021
DOI: 10.1038/s41390-021-01556-w
|View full text |Cite
|
Sign up to set email alerts
|

Odor-active volatile compounds in preterm breastmilk

Abstract: Background Volatile compounds in breastmilk (BM) likely influence flavor learning and, through the cephalic phase response, metabolism, and digestion. Little is known about the volatile compounds present in preterm BM. We investigated whether maternal or infant characteristics are associated with the profile of volatile compounds in preterm BM. Methods Using solid-phase microextraction coupled with gas chromatography/mass spectrometry, we analyzed volatile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The concentrations we report are, however, similar to one study involving extremely and very preterm infants ( 13 ). We previously have demonstrated that medium chain fatty acids and metabolic hormones in preterm HM differed by maternal ethnicity ( 54 , 55 ) but it is unclear if ethnicity influences the concentration of GCs in HM. Despite the multi-ethnic population, our study is not fully representative of the general population of woman giving birth in New Zealand ( 56 ), with Māori and Caucasian mothers being under-represented and Asian and Pacific mothers over-represented compared to the national birthing population.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations we report are, however, similar to one study involving extremely and very preterm infants ( 13 ). We previously have demonstrated that medium chain fatty acids and metabolic hormones in preterm HM differed by maternal ethnicity ( 54 , 55 ) but it is unclear if ethnicity influences the concentration of GCs in HM. Despite the multi-ethnic population, our study is not fully representative of the general population of woman giving birth in New Zealand ( 56 ), with Māori and Caucasian mothers being under-represented and Asian and Pacific mothers over-represented compared to the national birthing population.…”
Section: Discussionmentioning
confidence: 99%
“…In the same context, breast milk samples were collected from 170 mothers (breastfeeding premature infants) and analyzed by Muelbert and colleagues [71], with SPME-GC-MS revealing the presence of VOCs such as toluene, styrene, benzene and ethyl benzene, which were also detected in the present work (with the exception of ethylbenzene as a parent). Nevertheless, quantitative data were not provided (only relative quantitation) to compare them with the findings of this work.…”
Section: Discussionmentioning
confidence: 55%
“…Results of this study predict that many volatile terpenes from the essential oils are transferred into breast milk selectively. Our model helps to explain and expand on the current knowledge of volatile compounds in breast milk by predicting that a variety of volatile terpenoids can be found in breast milk 6,62 …”
Section: Discussionmentioning
confidence: 99%